The Determination of Preventive Maintenance using Simulated Annealing Algorithm Based on Weighted Fitness Function - Franty, Yeny Krista; Handoko, Budhi (Department Industrial Engineering, University of Muhammadiyah Malang, 2019)
This study aims to determine the machine maintenance schedule. We use the Simulated Annealing Algorithm. Fitness and reliability functions are functions that are used in the optimization process. Several weighting scenarios are done to see the unity of the function. The results of the scenario produce several alternative schedules. This algorithm is implemented on machines that have more than one sub-machine. This sub-machine is a smaller engine system part. This sub-machine also has one particular function. The results of the study show that the optimal engine maintenance period to use is six periods. There are five scheduling scenarios used in this problem. The resulting schedule can increase the value of reliability and can minimize costs.